Hexagonal geospatial model of landscape diversity in the northern sub‐area of the Volga River Delta landscape, Russia - V. V. Zanozin; A. N. Barmin; V. V. Zanozin; S. A. Yamashkin; V. A. Koren; E. V. Zanozina (Юг России: экология, развитие)
The aim is to analyse the landscape diversity (LD) of the northern sub‐area of the Volga River delta landscape using a series of mathematical operations.The work is based on full‐stack landscape works including field experiments. Descriptive method, GIS‐analysis and remote sensing data were used in the work.A set of landscape diversity indices was calculated for the northern sub‐area of the Volga Delta landscape on the basis of mathematical apparatus and the entropic complexity of landscape pattern (or Shannon diversity index) of the studied region was estimated. The results of the analysis made it possible to identify two habitats with rather high landscape diversity indices in this region.LD is one of the most important geographical characteristics of the region and allows assessment of the stability of geosystems to anthropogenic loads, reflection on the nature of economic development and use of geosystems and their conservation potential. By comparing HR indicators and retrospective analysis of economic development of the Volga River Delta, it was found that areas with low landscape diversity index were more often used for agriculture, as single large tracts are easier to adapt to economic needs. Areas with a complex morphological structure and, accordingly, a high level of landscape diversity are generally not subject to most types of economic impact.